Validation of Evapotranspiration Prediction Model: An Effort to Complete the National Climate Database System - ELEONORA RUNTUNUWU; HARIS SYAHBUDDIN; ARIS PRAMUDIA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2008)
To cope with limited evapotranspiration data, recently, there are many evapotranspiration estimation methods have been developed. Those methods were generally developed in sub tropic region when climate is not similar with Indonesia and the methods may not be applied directly. Validation of several estimation methods including Blaney Criddle, Radiation, Penman, and Pan Evaporation have been done in Cikarawang (Bogor) and Ciledug (Tangerang). The average correction factor andcorrelation coefficient (r) were respectively 1.83 for Blaney Criddle method (r = 0.97); 1.90 for Radiation method (r=0.97); 1.10 for Penman method (r=0.96), and 1.81 for Pan Evaporation method (r=0.98). Penman is the best method with regard on the smallest correction factor especially for station with complete climatic data. Since all methods have correlationcoefficient of more than 0.95, those methods can be used to estimate evapotranspiration based on the available climatic data. The present study used the Penman and Pan Evaporation methods to estimate evapotranspiration in Bogor for period of 1995-2005. The study provides insight into alternative to estimate the evapotranspiration for the area with no lysimeter. The method is selected by considering the available climatic data.